Appropriate Number of Sex Pheromone Trap for Monitoring Spodoptera exigua Hubner (Lepidoptera: Noctuidae) Moths on Shallot Field - Dian Lestari; F. X. Wagiman; Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 2020)
The research was carried out to determine the appropriate number of sex pheromone traps for monitoring the Spodoptera exigua moths in shallot crop which was grown in Yogyakarta Special Territory, Bantul Regency (Samas). This research was conducted in August until September 2016. Sex pheromone trap was arranged on shallot aged  3 weeks after planting. Sex pheromone trap with hexadecenat tetra asetat ingredients was placed on sticky yellow trap. This research  used RCBD experimental design with single factor experiment namely the number of trap i.e. 3, 5, 6, 8 units/2.000 m2 with sex pheromone, and  three traps without sex pheromone as control. Each treatment was repeated 5 times so  125 samples of experiments were obtained. Observation was made by counting the number of moths caught in sex pheromone trap. The result of observation was analysed  with analysis of variance (ANOVA) and DMRT α 5.0%. The results show that the appropriate number of trap to monitor the pest infestation was 3 units/2.000 m2.